Hot melt adhesive for automotive interior parts and preparation method thereof

By compounding a core-shell structure modified matrix resin with hydrogenated petroleum resin, a polyamide-polyacrylate interpenetrating network structure is formed, which solves the problem of poor adhesion of traditional hot melt adhesives to low surface energy materials and achieves high-strength adhesion and temperature resistance to a variety of automotive interior component substrates.

CN122234738APending Publication Date: 2026-06-19GUANGDONG PROVINCE EAGLE FLYING PLASTIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610677624.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-18
Publication Date
2026-06-19
Patent Text Reader

Abstract

This invention relates to a hot melt adhesive for automotive interior parts and its preparation method, comprising the following components: 45-60 parts of modified matrix resin; 12-20 parts of hydrogenated petroleum resin; 10-12 parts of dodecyl lactam; 2-5 parts of silane coupling agent; 2-5 parts of nano-silica; 0.5-1 parts of dehydrating agent; and 0.2-0.5 parts of catalyst. The modified matrix resin is prepared by adding amide-containing monomers to an acrylate core emulsion and performing a polymerization reaction to obtain the modified matrix resin, wherein the core-shell mass ratio of the modified matrix resin is 5:5 to 6:4. The modified matrix resin with a core-shell structure is combined with dodecyl lactam and catalyst to form a polyamide-polyacrylate interpenetrating network structure, giving the hot melt adhesive good adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hot melt adhesive technology, and in particular to a hot melt adhesive for automotive interior parts and its preparation method. Background Technology

[0002] The bonding of automotive interior components is a crucial step in the automobile manufacturing process, involving the assembly of various parts such as dashboards, door panels, headliners, and seats. Traditional adhesives used in automotive interiors mainly include solvent-based adhesives, water-based adhesives, and hot melt adhesives. Among them, hot melt adhesives are widely used in the automotive interior industry due to their advantages such as fast curing speed, no solvent evaporation, good environmental performance, and ease of automated application.

[0003] Traditional hot melt adhesives typically use polyamide as the base resin. While polyamide-based hot melt adhesives have good temperature resistance, they do not perform well in bonding low surface energy materials (such as polypropylene). Summary of the Invention

[0004] Therefore, it is necessary to provide a hot melt adhesive for automotive interior parts and its preparation method to address the problem of poor adhesion of hot melt adhesives.

[0005] In a first aspect, the present invention provides a hot melt adhesive for automotive interior parts, comprising the following components by weight: 45-60 parts of modified matrix resin; 12-20 parts of hydrogenated petroleum resin; 10-12 parts of dodecanoic acid; 2-5 parts of silane coupling agent; 2-5 parts of nano-silica; 0.5-1 part of dehydrating agent; Catalyst 0.2-0.5 parts; The modified matrix resin is prepared by the following method: A modified matrix resin is obtained by adding amide-containing monomers to an acrylate core emulsion and carrying out a polymerization reaction. The core-shell mass ratio of the modified matrix resin is 5:5 to 6:4.

[0006] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that the modified matrix resin is prepared by the following method: Add 5-8 parts of emulsifier (sodium dodecyl diphenyl ether disulfonate) and 0.3-0.5 parts of sodium bicarbonate to 150-160 parts by weight of deionized water. After stirring and dissolving, raise the temperature to 75-85°C and continuously add 30-35 parts of butyl acrylate, 28-32 parts of methyl methacrylate and 0.3-0.5 parts of ammonium persulfate for 2-3 hours. Stir for 25-35 minutes to obtain an acrylate core emulsion. 25-30 parts of butyl acrylate, 0.2-0.5 parts of ammonium persulfate, 15-20 parts of isooctyl acrylate, 8-11 parts of hydroxyethyl acrylate, 8-12 parts of N-vinylcaprolactam, 0.2-0.5 parts of n-dodecyl mercaptan, and 3-6 parts of N-(6-aminohexyl)acrylamide were continuously added dropwise to an acrylate core emulsion for 2-3 hours. After maintaining the temperature for 1-1.5 hours, 0.1-0.2 parts of ammonium persulfate were added, and the temperature was raised to 80-85℃ and reacted for 30-50 minutes. After demulsification, washing, dehydration, and drying, the modified matrix resin was obtained.

[0007] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that the core-shell mass ratio of the modified matrix resin is 6:4.

[0008] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that the weight ratio of the modified matrix resin to the hydrogenated petroleum resin is (3~4):1.

[0009] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that the dehydrating agent is a molecular sieve and carbodiimide, the weight ratio of the molecular sieve and carbodiimide is 1:(0.3~0.5), and the molecular sieve particle size is <0.5m.

[0010] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that the catalyst is one or more of phosphoric acid, sodium caprolactam, and N-acetylcaprolactam.

[0011] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that, by weight, it further comprises: 0.5-1.5 parts of antioxidant.

[0012] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that the antioxidant is one or more of hindered phenol, phosphite and zinc stearate.

[0013] In one embodiment, the hot melt adhesive for automotive interior parts according to claim 1 is characterized in that it further comprises: 0.3-0.8 parts of ultraviolet absorber.

[0014] Secondly, the present invention provides a method for preparing a hot melt adhesive for automotive interior parts, used to prepare the hot melt adhesive of any of the above embodiments, comprising the following steps: For pretreatment of nano-silica, 2-5 parts of silane coupling agent are diluted with 8-10 parts of ethanol, and stirred with 2-5 parts of nano-silica at 80℃-85℃ for 1.5-3 hours. After drying, pretreated nano-silica is obtained. The modified matrix resin, hydrogenated petroleum resin, pretreated nano silica, and dehydrating agent are melt-blended at 150-160℃ for 10-15 minutes to obtain the first mixture. The first mixture is cooled to 120-125℃, and antioxidants and ultraviolet absorbers are added. The mixture is then melt-blended for another 10-15 minutes to obtain the second mixture. Add pre-molten dodecyl lactam and catalyst to the second mixture, heat to 250-280℃ and stir for 30-45 minutes. After vacuum devolatilization, perform underwater granulation to obtain hot melt adhesive.

[0015] The aforementioned hot melt adhesive for automotive interior parts is prepared by core-shell emulsion polymerization to obtain a modified matrix resin with a core-shell structure. The core-shell mass ratio is controlled within the range of 5:5 to 6:4, giving the resin both flexibility and temperature resistance. Simultaneously, the polar groups in the shell can form hydrogen bonds and coordination bonds with various substrate surfaces, significantly improving its adaptability to both low surface energy materials (such as polypropylene) and high surface energy materials (such as metals and glass). Hydrogenated petroleum resin exhibits excellent aging resistance and color stability, and shows good compatibility with the modified matrix resin, improving wettability and initial tack to various substrates. Dodecyl lactam and a catalyst can form a polyamide-polyacrylate interpenetrating network structure with the modified matrix resin, giving the hot melt adhesive both flexibility and high strength, as well as oil resistance, significantly improving its temperature resistance. Combining nano-silica, silane coupling agents, and other additives can improve the mechanical strength, heat resistance, and dimensional stability of the hot melt adhesive. A dehydrating agent effectively inhibits the hydrolytic degradation of polyamide during high-temperature processing, maintaining product stability.

[0016] In addition, the core layer of the modified matrix resin is mainly composed of butyl acrylate and methyl methacrylate copolymer, which provides good cohesive strength and toughness. The shell layer introduces amide-containing monomers (N-vinylcaprolactam, N-(6-aminohexyl)acrylamide), hydroxyethyl acrylate and isooctyl acrylate, which endow the resin with polar groups (amide groups, hydroxyl groups) and flexible long-chain alkyl groups, thereby enhancing the adhesiveness of the hot melt adhesive while improving its flexibility. Detailed Implementation

[0017] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0018] Preparation Example 1 Add 150 parts of deionized water to a reaction vessel, along with 5 parts of sodium dodecyl diphenyl ether disulfonate and 0.3 parts of sodium bicarbonate. After stirring and dissolving, heat to 75°C. Mix 30 parts of butyl acrylate, 28 parts of methyl methacrylate, and 0.3 parts of ammonium persulfate thoroughly, and then continuously add the mixture dropwise to the reaction vessel over 2 hours. After the addition is complete, continue stirring for 25 minutes to obtain an acrylate core emulsion.

[0019] 25 parts butyl acrylate, 0.2 parts ammonium persulfate, 15 parts isooctyl acrylate, 8 parts hydroxyethyl acrylate, 8 parts N-vinylcaprolactam, 0.2 parts n-dodecyl mercaptan, and 3 parts N-(6-aminohexyl)acrylamide were continuously added dropwise to the above acrylate core emulsion over a period of 2 hours. After the addition was complete, the mixture was kept at this temperature for 1 hour. Then, 0.1 parts ammonium persulfate was added, and the temperature was raised to 80°C for 30 minutes. After the reaction was completed, calcium chloride solution was added to demulsify the emulsion. After demulsification, the mixture was washed three times with deionized water, dehydrated, and then vacuum dried at 60°C for 12 hours to obtain the modified matrix resin.

[0020] The core-shell mass ratio of the modified matrix resin in Preparation Example 1 was determined to be approximately 5.5:4.5.

[0021] Preparation Example 2 155 parts of deionized water were added to a reaction vessel, along with 6.5 parts of sodium dodecyl diphenyl ether disulfonate and 0.4 parts of sodium bicarbonate. After stirring and dissolving, the mixture was heated to 80°C. 33 parts of butyl acrylate, 30 parts of methyl methacrylate, and 0.4 parts of ammonium persulfate were mixed thoroughly and then continuously added dropwise to the reaction vessel over 2.5 hours. After the addition was complete, stirring was continued for 30 minutes to obtain an acrylate core emulsion.

[0022] 27.5 parts butyl acrylate, 0.3 parts ammonium persulfate, 18 parts isooctyl acrylate, 9.5 parts hydroxyethyl acrylate, 10 parts N-vinylcaprolactam, 0.3 parts n-dodecyl mercaptan, and 5 parts N-(6-aminohexyl)acrylamide were continuously added dropwise to the above acrylate core emulsion over a period of 2.5 hours. After the addition was complete, the mixture was kept at this temperature for 1.25 hours. Then, 0.15 parts ammonium persulfate were added, and the temperature was raised to 82°C for 40 minutes. After the reaction was completed, calcium chloride solution was added to demulsify the emulsion. After demulsification, the mixture was washed three times with deionized water, dehydrated, and then vacuum dried at 60°C for 12 hours to obtain the modified matrix resin.

[0023] The core-shell mass ratio of the modified matrix resin in Preparation Example 2 was determined to be approximately 6:4.

[0024] Preparation Example 3 160 parts of deionized water were added to a reaction vessel, along with 8 parts of sodium dodecyl diphenyl ether disulfonate and 0.5 parts of sodium bicarbonate. After stirring and dissolving, the mixture was heated to 85°C. 35 parts of butyl acrylate, 32 parts of methyl methacrylate, and 0.5 parts of ammonium persulfate were mixed thoroughly and then continuously added dropwise to the reaction vessel over 3 hours. After the addition was complete, stirring was continued for 35 minutes to obtain an acrylate core emulsion.

[0025] 30 parts butyl acrylate, 0.5 parts ammonium persulfate, 20 parts isooctyl acrylate, 11 parts hydroxyethyl acrylate, 12 parts N-vinylcaprolactam, 0.5 parts n-dodecyl mercaptan, and 6 parts N-(6-aminohexyl)acrylamide were continuously added dropwise to the above acrylate core emulsion over a period of 3 hours. After the addition was complete, the mixture was kept at this temperature for 1.5 hours. Then, 0.2 parts ammonium persulfate were added, and the temperature was raised to 85°C and the reaction was carried out for 50 minutes. After the reaction was completed, calcium chloride solution was added to demulsify the emulsion. After demulsification, the mixture was washed three times with deionized water, dehydrated, and then vacuum dried at 60°C for 12 hours to obtain the modified matrix resin.

[0026] The core-shell mass ratio of the modified matrix resin in Preparation Example 3 was determined to be approximately 6:4.

[0027] Comparative preparation example Add 150 parts of deionized water to a reaction vessel, along with 5 parts of sodium dodecyl diphenyl ether disulfonate and 0.3 parts of sodium bicarbonate. After stirring and dissolving, heat to 75°C. Mix 20 parts of butyl acrylate, 18 parts of methyl methacrylate, and 0.3 parts of ammonium persulfate thoroughly, and then continuously add the mixture dropwise to the reaction vessel over 2 hours. After the addition is complete, continue stirring for 25 minutes to obtain an acrylate core emulsion.

[0028] 45 parts butyl acrylate, 0.2 parts ammonium persulfate, 30 parts isooctyl acrylate, 8 parts hydroxyethyl acrylate, 8 parts N-vinylcaprolactam, 0.2 parts n-dodecyl mercaptan, and 3 parts N-(6-aminohexyl)acrylamide were continuously added dropwise to the above acrylate core emulsion over a period of 2 hours. After the addition was complete, the mixture was kept at this temperature for 1 hour. Then, 0.1 parts ammonium persulfate was added, and the temperature was raised to 80°C and reacted for 30 minutes. After the reaction was completed, calcium chloride solution was added to demulsify the emulsion. After demulsification, the mixture was washed three times with deionized water, dehydrated, and then vacuum dried at 60°C for 12 hours to obtain the modified matrix resin.

[0029] The core-shell mass ratio of the modified matrix resin in Preparation Example 1 was determined to be approximately 3:7.

[0030] Example 1: S1: Pretreatment of nano-silica. 3.5 parts of silane coupling agent KH-570 were diluted with 10 parts of ethanol and mixed with 3 parts of nano-silica (particle size approximately 30 nm). The mixture was stirred at 82°C for 2 hours and dried to obtain pretreated nano-silica. Vacuum drying was performed at 90°C, resulting in a moisture content of <0.3% after dehydration.

[0031] S2: 52.5 parts of the modified matrix resin prepared in Preparation Example 1, 16 parts of hydrogenated petroleum resin (softening point 100℃), 3.5 parts of pretreated nano-silica, and 0.75 parts of dehydrating agent (wherein the molecular sieve to carbodiimide weight ratio is 1:0.4, and the molecular sieve particle size is 0.3m) were added to a mixer and melt-blended at 155℃ for 12 minutes to obtain the first mixture; S3: Cool the first mixture to 122°C, add 1 part of antioxidant (hindered phenol and phosphite weight ratio 1:1) and 0.4 parts of UV absorber UV-531, and continue to melt and blend for 12 minutes to obtain the second mixture; S4: Add 11 parts of pre-melted dodecyl lactam and 0.35 parts of catalyst (sodium caprolactam) to the second mixture, heat to 265°C and stir for 30 minutes, vacuum devolatilize (vacuum degree -0.09MPa, time 10 minutes), and then perform underwater granulation to obtain hot melt adhesive particles.

[0032] Example 2: The difference from Example 1 is that the modified matrix resin prepared in Preparation Example 2 was used.

[0033] Example 3: The difference from Example 1 is that the modified matrix resin prepared in Preparation Example 3 was used.

[0034] Example 4: S1: Pretreatment of nano-silica. Two parts of silane coupling agent KH-570 were diluted with eight parts of ethanol and stirred with two parts of nano-silica (particle size approximately 30 nm) at 85°C for 1.5 hours. After drying, pretreated nano-silica was obtained. Vacuum drying was performed at 95°C, resulting in a moisture content of <0.3% after dehydration.

[0035] S2: 60 parts of the modified matrix resin prepared in Preparation Example 1, 20 parts of hydrogenated petroleum resin (softening point 100℃), 5 parts of pretreated nano-silica, and 0.5 parts of dehydrating agent (wherein the molecular sieve to carbodiimide weight ratio is 1:0.5, and the molecular sieve particle size is 0.4m) were added to a mixer and melt-blended at 160℃ for 10 minutes to obtain the first mixture; S3: Cool the first mixture to 125°C, add 1.5 parts of antioxidant (hindered phenol and phosphite in a weight ratio of 1:1) and 0.5 parts of UV absorber UV-531, and continue to melt and blend for 10 minutes to obtain the second mixture; S4: Add 12 parts of pre-melted dodecyl lactam and 0.2 parts of catalyst (sodium caprolactam and N-acetylcaprolactam, weight ratio 1:1) to the second mixture, heat to 250°C and stir for 45 minutes. After vacuum devolatilization (vacuum degree -0.08MPa, time 10 minutes), perform underwater granulation to obtain hot melt adhesive particles.

[0036] Example 5: S1: Pretreatment of nano-silica. 5 parts of silane coupling agent KH-570 were diluted with 9 parts of ethanol and stirred with 5 parts of nano-silica (particle size approximately 30 nm) at 80°C for 3 hours. After drying, pretreated nano-silica was obtained. Vacuum drying was performed at 85°C, resulting in a moisture content of <0.3% after dehydration.

[0037] S2: 45 parts of the modified matrix resin prepared in Preparation Example 1, 12 parts of hydrogenated petroleum resin (softening point 100℃), 2 parts of pretreated nano-silica, and 1 part of molecular sieve dehydrating agent (molecular sieve to carbodiimide weight ratio 1:0.3, molecular sieve particle size 0.2m) were added to a mixer and melt-blended at 150℃ for 15 minutes to obtain the first mixture; S3: Cool the first mixture to 120°C, add 0.5 parts of antioxidant zinc stearate and 0.3 parts of ultraviolet absorber UV-531, and continue to melt and blend for 15 minutes to obtain the second mixture; S4: Add 10 parts of pre-melted dodecyl lactam and 0.5 parts of catalyst phosphoric acid to the second mixture, heat to 280°C and stir for 45 minutes, vacuum devolatilize (vacuum degree -0.09MPa, time 15 minutes), and then perform underwater granulation to obtain hot melt adhesive particles.

[0038] Comparative Example 1 The difference from Example 1 is that polyamide resin is used as the matrix resin.

[0039] Comparative Example 2 The difference from Example 1 is as follows: S4 heats the second mixture to 265°C and stirs for 30 minutes. After vacuum devolatilization (vacuum degree -0.09MPa, time 10 minutes), it is granulated underwater to obtain hot melt adhesive particles.

[0040] Comparative Example 3 The difference from Example 1 is that the modified matrix resin prepared in the comparative preparation example is used.

[0041] Application Example 1 The hot melt adhesive prepared in Example 1 was used to bond the dashboard skin (PVC / fabric composite layer) of a certain vehicle model to the metal frame. The hot melt adhesive was melted at 180°C and sprayed onto the surface of the metal frame at a spraying amount of 130 g / m. Then the skin was bonded together and hot-pressed for 20 seconds at 0.4 MPa and 80°C.

[0042] Application Example 2 The difference from Application Example 1 is that the hot melt adhesive prepared in Example 2 is used.

[0043] Application Example 3 The difference from Application Example 1 is that the hot melt adhesive prepared in Example 3 is used.

[0044] Application Example 4 The difference from Application Example 1 is that the hot melt adhesive prepared in Example 4 is used.

[0045] Application Example 5 The difference from Application Example 1 is that the hot melt adhesive prepared in Example 5 is used.

[0046] Application Example 6 The hot melt adhesive prepared in Example 2 was used to bond the fabric to a polypropylene (PP) substrate in an automotive door panel interior panel. The hot melt adhesive was applied by roller coating at a rate of 120 g / m², and after bonding, it was hot-pressed at 0.3 MPa and 75°C for 15 seconds.

[0047] Application Example 7 The difference from Application Example 6 is that the hot melt adhesive prepared in Example 2 is used.

[0048] Application Example 8 The difference from Application Example 6 is that the hot melt adhesive prepared in Example 3 is used.

[0049] Application Example 9 The difference from Application Example 6 is that the hot melt adhesive prepared in Example 4 is used.

[0050] Application Example 10 The difference from Application Example 6 is that the hot melt adhesive prepared in Example 5 is used.

[0051] Comparative Application Example 1 The difference from Application Example 1 is that the hot melt adhesive prepared in Comparative Example 1 is used.

[0052] Comparative Application Example 2 The difference from Application Example 1 is that the hot melt adhesive prepared in Comparative Example 2 is used.

[0053] Comparative Application Example 3 The difference from Application Example 1 is that the hot melt adhesive prepared in Comparative Example 3 is used.

[0054] Comparative Application Example 4 The difference from Application Example 1 is that the hot melt adhesive prepared in Comparative Example 1 is used.

[0055] Comparative Application Example 5 The difference from Application Example 1 is that the hot melt adhesive prepared in Comparative Example 2 is used.

[0056] Comparative Application Example 6 The difference from Application Example 1 is that the hot melt adhesive prepared in Comparative Example 3 is used.

[0057] Performance testing 1. Peel strength test Test specimens with a width of 25 mm and a length of 150 mm were prepared for Application Examples 1-10 and Comparative Application Examples 1-6. The specimens were placed in a standard environment (temperature 232°C, relative humidity 50.5%) for 72 hours before testing. Test speed: 100 mm / min, peel angle: 180°, test temperature: 232°C. Test method: Peel approximately 50 mm off one end of the specimen and clamp it in the upper and lower fixtures of the universal testing machine. Start the testing machine and peel at a constant speed for 180°, recording the force-displacement curve during the peeling process. The peel strength is taken as the average force value of the stable segment of the curve, in N / 25 mm. Five specimens are tested consecutively, and the arithmetic mean is taken. The test results are shown in Tables 1 and 2.

[0058] 2. Softening point test The test was conducted according to GB / T 15332-1994, "Determination of Softening Point of Hot Melt Adhesives - Ring and Ball Method". The test results are shown in Table 3.

[0059] 3. Melt viscosity test The hot melt adhesive particles prepared in Examples 1-5 and Comparative Examples 1-3 were added to the heating chamber of the Brookfield viscometer and heated to the target test temperature. The temperature was kept constant for 15 minutes to allow the sample to completely melt and reach thermal equilibrium.

[0060] Select a suitable rotor and insert it into the molten adhesive to the specified depth. Rotate the rotor at 20 rpm and record the viscosity value after the reading stabilizes. Test three times at each temperature point and take the average value. The test results are shown in Table 3.

[0061] Table 1: Test Data Table for Application Examples 1-5 and Comparative Application Examples 1-3 Application Example 1 Application Example 2 Application Example 3 Application Example 4 Application Example 5 Comparative Application Example 1 Comparative Application Example 2 Comparative Application Example 3 Peel strength (N / 25mm) 88 89 87 84 82 69 67 77 Table 2: Test data for Application Examples 6-10 and Comparative Application Examples 4-6 Application Example 6 Application Example 7 Application Example 8 Application Example 9 Application Example 10 Comparative Application Example 4 Comparative Application Example 5 Comparative Application Example 6 Peel strength (N / 25mm) 84 85 84 81 80 65 61 71 Table 3: Test Data Tables for Examples 1-5 and Comparative Examples 1-3 Softening point (°C) Melt viscosity (180℃, mPas) Example 1 170 4482 Example 2 172 4550 Example 3 173 4363 Example 4 165 4215 Example 5 163 4302 Comparative Example 1 151 3856 Comparative Example 2 142 3762 Comparative Example 3 155 3951 As can be seen from Examples 1-10 and Application Examples 1-10, the hot melt adhesive protected by this application has good adhesion to a variety of automotive interior substrates (such as low surface energy materials like polypropylene PP and high surface energy materials like metals), and also has high adhesive strength, making it widely applicable.

[0062] By comparing Examples 1-5 with Comparative Example 1, Application Examples 1-5 with Comparative Application Example 1, and Application Examples 6-10 with Comparative Application Example 4, it can be seen that the present invention, through the core-shell structure modification of the matrix resin and the compounding of dodecyl lactam and catalyst, forms a polyamide-polyacrylate interpenetrating network structure, which makes the hot melt adhesive both flexible and strong. The hot melt adhesive has good temperature resistance, with a softening point in the range of 168-175℃ and a melt viscosity in the range of 4200-4600mPas. The viscosity is moderate, and it has good processability in the process of assembling automotive interiors.

[0063] By comparing Examples 1-5 with Comparative Example 2, Application Examples 1-5 with Comparative Application Example 2, and Application Examples 6-10 with Comparative Application Example 5, it can be seen that when a polyamide-polyacrylate interpenetrating network structure is not formed in the hot melt adhesive, the softening point of the hot melt adhesive is significantly reduced and the bonding performance deteriorates.

[0064] By comparing Examples 1-5 with Comparative Example 3, Application Examples 1-5 with Comparative Application Example 3, and Application Examples 6-10 with Comparative Application Example 6, it can be seen that a core-shell ratio of the modified matrix resin exceeding the range of 5:5 to 6:4 will lead to a decrease in resin cohesive strength, a decrease in softening point, and a decrease in adhesive strength.

[0065] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0066] The above embodiments merely illustrate several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A hot melt adhesive for automotive interior parts, characterized in that, By weight, it includes the following components: 45-60 parts of modified matrix resin; 12-20 parts of hydrogenated petroleum resin; 10-12 parts of dodecanoic acid; 2-5 parts of silane coupling agent; 2-5 parts of nano-silica; 0.5-1 part of dehydrating agent; Catalyst 0.2-0.5 parts; The modified matrix resin is prepared by the following method: The modified matrix resin is obtained by adding amide-containing monomers to an acrylate core emulsion and carrying out a polymerization reaction, wherein the core-shell mass ratio of the modified matrix resin is 5:5 to 6:

4.

2. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, The modified matrix resin is prepared by the following method: Add 5-8 parts of emulsifier (sodium dodecyl diphenyl ether disulfonate) and 0.3-0.5 parts of sodium bicarbonate to 150-160 parts by weight of deionized water. After stirring and dissolving, raise the temperature to 75-85°C, and continuously add 30-35 parts of butyl acrylate, 28-32 parts of methyl methacrylate and 0.3-0.5 parts of ammonium persulfate for 2-3 hours. Stir for 25-35 minutes to obtain the acrylate core emulsion. 25-30 parts of butyl acrylate, 0.2-0.5 parts of ammonium persulfate, 15-20 parts of isooctyl acrylate, 8-11 parts of hydroxyethyl acrylate, 8-12 parts of N-vinylcaprolactam, 0.2-0.5 parts of n-dodecyl mercaptan, and 3-6 parts of N-(6-aminohexyl)acrylamide were continuously added dropwise to the acrylate core emulsion for 2-3 hours. After maintaining the temperature for 1-1.5 hours, 0.1-0.2 parts of ammonium persulfate were added, and the temperature was raised to 80-85°C and reacted for 30-50 minutes. After demulsification, washing, dehydration, and drying, the modified matrix resin was obtained.

3. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, The core-shell mass ratio of the modified matrix resin is 6:

4.

4. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, The weight ratio of the modified matrix resin to the hydrogenated petroleum resin is (3~4):

1.

5. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, The dehydrating agent is a molecular sieve and carbodiimide, wherein the weight ratio of the molecular sieve to carbodiimide is 1:(0.3~0.5), and the molecular sieve particle size is <0.5m.

6. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, The catalyst is one or more of phosphoric acid, sodium caprolactam, and N-acetylcaprolactam.

7. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, It also includes, by weight, 0.5-1.5 parts of antioxidant.

8. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, The antioxidant is one or more of hindered phenols, phosphites, and zinc stearate.

9. The hot melt adhesive for automotive interior parts according to claim 1, characterized in that, Also includes: 0.3-0.8 parts of UV absorber.

10. A method for preparing a hot melt adhesive for automotive interior parts, used to prepare the hot melt adhesive according to any one of claims 1-9, characterized in that, For pretreatment of nano-silica, 2-5 parts of silane coupling agent are diluted with 8-10 parts of ethanol, and stirred with 2-5 parts of nano-silica at 80℃-85℃ for 1.5-3 hours. After drying, pretreated nano-silica is obtained. The modified matrix resin, hydrogenated petroleum resin, pretreated nano silica, and dehydrating agent are melt-blended at 150-160℃ for 10-15 minutes to obtain the first mixture. The first mixture is cooled to 120-125℃, and antioxidants and ultraviolet absorbers are added. The mixture is then melt-blended for another 10-15 minutes to obtain the second mixture. Add pre-molten dodecyl lactam and catalyst to the second mixture, heat to 250-280℃ and stir for 30-45 minutes, vacuum devolatilize and then granulate underwater to obtain the hot melt adhesive.